The all England law reports reprint. (London : Butterworth, 1957)
Vols. for 1558-1834 selected from early authorised reports; v. for 1 835-1935 selected from the Law times reports.
Updated irregularly by extension vols.
Some vols. published out of sequence.
Includes an Index (1558-1935)
1558-1834. 1 v.; Extension vol. 1861-1935. 1 v.; Extension vol. 1904 -1935. 1 v.
Keywords: Law reports, digests, etc. -- Great Britain